2002
DOI: 10.1094/phyto.2002.92.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Pathogenic, and Molecular Characterization of Alternaria Isolates Associated with Alternaria Late Blight of Pistachio

Abstract: Alternaria isolates were obtained from various pistachio tissues collected in five orchards in California. For all isolates, morphological characteristics of the colony and sporulation apparatus were determined and compared with those of representative isolates of A. alternata, A. tenuissima, A. arborescens, and A. infectoria. A selection of the pistachio isolates and the representative Alternaria isolates were evaluated for pathogenicity to pistachio. Molecular characteristics of these isolates were determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
180
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(198 citation statements)
references
References 20 publications
16
180
1
1
Order By: Relevance
“…Many researchers have found this fungus to be a common pathogen on a number of plants in different parts of the world. It can, for example, induce late blight of pistachio in the USA (Pryor and Michailides 2002), and was established as a major cause of apple dry core rot in South Africa (Serdani et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have found this fungus to be a common pathogen on a number of plants in different parts of the world. It can, for example, induce late blight of pistachio in the USA (Pryor and Michailides 2002), and was established as a major cause of apple dry core rot in South Africa (Serdani et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have reported that differentiation of the small-spored Alternaria spp. is difficult due to lack of variation in nuclear ribosomal ITS and β-tubulin sequences, two genomic regions typically used in fungal systematic 17,27 . The A. alternata population of tangerine in Jahrom region orchards showed high morphological and genetic diversity, which may provide information on genetic differences among tangerine isolates from different cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…Much research has focused on identification of genetic differences among citrus-associated Alternaria spp. 11,[15][16][17] but little is known about genetic differences among Alternaria isolates from individual citrus species. The objective of this study was to clarify that Alternaria isolates collected from tangerine cultivars had genetic differences (based on ITS sequences).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of Alternaria strains was isolated from different hosts including grapes [3][4][5][6]. Species such as Alternaria alternata, A. arborescens and A. tenuissima have frequently been isolated from grapes during development in the vineyard or postharvest storage [4,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%